2013
DOI: 10.1007/s40271-012-0001-0
|View full text |Cite
|
Sign up to set email alerts
|

Social Stigma in Diabetes

Abstract: A comprehensive understanding of the social and psychological impact of diabetes mellitus is important for informing policy and practice. One potentially significant, yet under-researched, issue is the social stigma surrounding diabetes. This narrative review draws on literature about health-related stigma in diabetes and other chronic conditions in order to develop a framework for understanding diabetes-related stigma. Our review of the literature found that people who do not have diabetes assume that diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
133
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 262 publications
(157 citation statements)
references
References 64 publications
7
133
0
11
Order By: Relevance
“…Additionally, Schabert, Browne, Mosely, and Speight found diabetes-related stigma was experienced across life domains, including at the workplace and in romantic relationships [19]. The same research found that diabetes-related stigma had a significant negative impact on psychosocial well-being; therefore, the social stigma associated with diabetes may partially account for the clinically significant levels of interpersonal distress found in this study.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Additionally, Schabert, Browne, Mosely, and Speight found diabetes-related stigma was experienced across life domains, including at the workplace and in romantic relationships [19]. The same research found that diabetes-related stigma had a significant negative impact on psychosocial well-being; therefore, the social stigma associated with diabetes may partially account for the clinically significant levels of interpersonal distress found in this study.…”
Section: Discussionsupporting
confidence: 64%
“…Furthermore, researchers experienced difficulty in the recruitment of males, minority populations, and those with low education levels. Due to the recent emergence of young adults with T2DM, the social stigma associated with T2DM, and the general difficulty recruiting minority populations (who are more likely to be diagnosed withT2DM) to participate in research, the sample size for this study is relatively small [19,21,22]. Generalizability to the larger population is therefore limited with these findings.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…(Vishwanath 2014). Der Vorwurf, die Betroffenen würden das Gesundheitswesen unnötig finanziell belasten, wie auch die Verwechslung mit Drogenabhängigen bestätigen Aussagen anderer kürzlich erschienener Studien Schabert et al 2013).…”
Section: Datenerfassung Und Auswertungunclassified
“…Gesichertes Wissen ist entsprechend gering (Schabert et al 2013). So hält etwa eine neuere, große internationale Studie zu psychosozialen Aspekten von Diabetes lediglich pauschal fest, dass Menschen mit Diabetes davon berichten, schon einmal diskriminiert worden zu sein (Wens et al 2013).…”
unclassified
See 1 more Smart Citation